BUDAYA INDIA DI MINANGKABAU STUDI ANALISIS TERHADAP ARTEFAK DI TANAH DATAR DAN WILAYAH SEKITARNYA - Bambang Budi Utomo; Sudarman Sudarman (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
In general, the influence of Indian culture embodied in the form of Hinduism and Buddhism developed in the western region of Nus?ntara. Archaeological evidence in the form of buildings ca??i / st?pa and statues, while historical data is written in inscriptions and manuscripts. The presence of Indian cultural influences was also found in the West Sumatra region in the form of sacred buildings from brick materials, and stone and metal statues. From historical sources, information was obtained that in the region had developed a royal institution which also had the influence of Indian culture. This study used a cultural history approach, not political history which is commonly used by most archaeologists and historians. The aim of this approach is to see the unity and unity among the Nus?ntara residents, especially the Minangkabau and other regions